2023
DOI: 10.21203/rs.3.rs-3014809/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metatranscriptomics of microbial biofilm succession on HDPE foil: uncovering plastic-degrading potential in soil communities

Abstract: Background Microbial communities in soil are a complex and sensitive system which secures soil health, nutrient cycling and the degradation of natural and xenobiotic substances. Even though plastic pollution is increasing worldwide, very little is known about microbial processes that take place once plastic debris gets incorporated into the soil matrix. In this study, we conducted the first metatranscriptome analysis of polyethylene (PE)-associated biofilm communities in a highly polluted landfill soil and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In addition to metagenomics, metatranscriptomics would be a useful method, as it indicates the expression of enzymatic machinery capable of plastic degradation. By applying metatranscriptomics to PE films, McLean et al [11] found a variety of plastic-associated genes (e.g. PETase), indicating the presence of potential enzymes for plastic degradation.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to metagenomics, metatranscriptomics would be a useful method, as it indicates the expression of enzymatic machinery capable of plastic degradation. By applying metatranscriptomics to PE films, McLean et al [11] found a variety of plastic-associated genes (e.g. PETase), indicating the presence of potential enzymes for plastic degradation.…”
Section: Plos Onementioning
confidence: 99%
“…There are many ways to find microbial enzymes that are potentially active in plastic degradation [8][9][10]. The most recently applied and innovative way to find an enzymatic machinery capable of plastic degradation is through metagenomics or metatranscriptomics [11]. While shotgun metagenomics extracts DNA from all cells in a community and then cuts it into tiny fragments that are sequenced independently [12], metatranscriptomics provides information about genes expressed by the community as a whole [13].…”
Section: Introductionmentioning
confidence: 99%